Pan-genus analysis and typing of antimicrobial resistance plasmids in Acinetobacter - Liam A. Tobin; Margaret M. C. Lam; Mehrad Hamidian (npj Antimicrobials and Resistance)
Abstract Plasmids play a central role in horizontal gene transfer and bacterial adaptation, especially in the context of antimicrobial resistance (AMR) among opportunistic pathogens. Some members of the genus Acinetobacter are known for their role in hospital-acquired infections, harboring plasmids that facilitate rapid adaptation to selective pressures. However, the extent of plasmid diversity and evolutionary dynamics within Acinetobacter has not been fully elucidated. In this study, we analysed 1846 complete and non-redundant Acinetobacter plasmid sequences, identifying 166 novel Replicase (Rep) protein types and providing a significant update to the Acinetobacter Plasmid Typing (APT) scheme, which now comprises 257 Rep types. A detailed phylogenetic analysis of the prevailing R3-type Rep sequences reveals two distinct evolutionary clades (A and B) and several additional subclades. This phylogenetic structure suggests evolutionary pressures within all clades, potentially influenced by host species distribution and environmental factors. Analysis of these plasmids highlights diverse plasmid types involved in dissemination of AMR within the genus in different niches, underscoring both clinical and natural environments as reservoirs of Acinetobacter plasmids. Our findings provide a refined framework for tracking Acinetobacter plasmids, advancing our understanding of plasmid-mediated AMR spread and informing strategies to combat the spread of AMR in this critical genus.